2007
DOI: 10.1103/physrevd.75.054012
|View full text |Cite
|
Sign up to set email alerts
|

Goldstone boson currents in a kaon condensed color-flavor locked phase

Abstract: We study the stability of the kaon condensed color-flavor locked (CFL) phase of dense quark matter with regard to the formation of a non-zero Goldstone boson current. In the kaon condensed phase there is an electrically charged fermion which becomes gapless near µ s . We find that the magnetic screening masses are real in the regime µ s < µs , but some screening masses are imaginary fors . We show that there is a very weak current instability for µ s > µs and a more robust instability in a small window near µs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Our results at T = 0 are in qualitative agreement with the effective field theory prediction that the first gapless mode in the CFLK 0 phase is electrically charged [37][38][39]. According to these works, there could be a second phase transition at lower chemical potential, where a neutral mode becomes gapless as well.…”
Section: A Phase Diagramsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results at T = 0 are in qualitative agreement with the effective field theory prediction that the first gapless mode in the CFLK 0 phase is electrically charged [37][38][39]. According to these works, there could be a second phase transition at lower chemical potential, where a neutral mode becomes gapless as well.…”
Section: A Phase Diagramsupporting
confidence: 90%
“…In Ref. [39] it was found that at T = 0 the gCFLK 0 * phase is reached from the ordinary gCFLK 0 phase in a first-order phase transition, where the condensate ∆ (s) 77 drops substantially. This is not very different from our CFLK 0 → gCFL phase transition, which is also first order and accompanied by a strong drop of ∆ (s) 77 .…”
Section: The Gcfl Window Between Normal and Cflk 0 Phasementioning
confidence: 99%
“…In fact, these situations get more complicated than the simple (T, µ) phase diagram, because they typically involve extremely large magnetic field ranging roughly 10 12 − 10 18 G (gauss), and the QCD matter can feature completely new behaviors under these conditions. Examples include magnetic catalysis [3], anomalous axial current in dense matter [4], chiral magnetic effect [5], new mechanism of pulsar kicks [6], spontaneous magnetization of neutron stars [7], etc to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…These values suggest that the kaons are condensed and thus that the relevant phase to consider is the CFL-K 0 phase. It has been argued that for sufficiently large values of the parameter m 2 s /µ q the CFL-K 0 phase is modified to the so-called curCFL-K 0 phase which is anisotropic and exhibits counter-propagating currents from the kaon condensate and ungapped fermions [43,44,45]. Because of the presence of ungapped fermions, the transport properties of this phase can be expected to be very different from the ones in the CFL-K 0 phase and similar to unpaired quark matter.…”
Section: A Chiral Lagrangianmentioning
confidence: 99%